Gypsies, ethnicity, and the labour market : an introduction - Casa-Nova, Maria José (2007)
The article reports on two years of ethnographic research carried out within a Gypsy community in an area on the outskirts of Porto, un northern Portugal. Data were colected during participating observation in labour environments (fairs) and residential settings (a council ward) as well as from interviews. The aim is to contribute to our knowledge and understanding of the lifestyle and opportunities of a particular community, in particular what employment means in this community and the relationship it establishes with the wider labour market. The data show (a) that capitalism of flexible accumulation affected the marginalized ethnic groups who live on the periphery of the system, and (b) that the relationship between a specific Portuguese Gypsy community and employment is mediated by ethnic belonging. Some crucial elements in the choice of occupation in this community are (a) independence through self- employment, which allows people to combine work with looking after the children and attention to intra-ethnic solidarity, and (b) the possibility of personal time management.